If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 = 96 + -8x Reorder the terms: -2 + 6x = 96 + -8x Solving -2 + 6x = 96 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -2 + 6x + 8x = 96 + -8x + 8x Combine like terms: 6x + 8x = 14x -2 + 14x = 96 + -8x + 8x Combine like terms: -8x + 8x = 0 -2 + 14x = 96 + 0 -2 + 14x = 96 Add '2' to each side of the equation. -2 + 2 + 14x = 96 + 2 Combine like terms: -2 + 2 = 0 0 + 14x = 96 + 2 14x = 96 + 2 Combine like terms: 96 + 2 = 98 14x = 98 Divide each side by '14'. x = 7 Simplifying x = 7
| 3x-6=-2x+24 | | 102-3x=4x+11 | | -3.5x=1.4 | | x+x+.65+x+.65+.36=10.90 | | -42-2x=12-8x | | 107-6x=8x+23 | | (x+4)+(52-x)=87 | | (x-4)+(52-x)=87 | | 206-3x=33x+22 | | -109-8x=8x+19 | | (2x+3)(2x+3.25)=15 | | x+5(x+1)=65 | | 6+4x=24+x | | 4x+8=-20-10x | | 6x+20=15x-79 | | 8x+6(-2x-2)=-10-6x | | 9x-19=3x+5 | | 3x+58=7x+14 | | 4x+7=27 | | 10x-13=77 | | 180-x=50+3(90-x) | | 180-x=50+3(90)-x | | 7d+4d+3d+9=3d | | -17-4x=7-8x | | -r-4-5r=-16 | | 5x+6=86-5x | | 155=n+137 | | 155=n | | 2(10a+3)-2=10-9a | | 8x+2+9x+3=180 | | -3(4b+1)=-4(-2+8b) | | 73=b-42 |